IMPACT OF BANKING SECTOR CREDITS ON ECONOMIC GROWTH IN NIGERIA (1991-2022) (Journal of the Management Sciences, 2024)
This study investigated the impact of Banking Sector Credits on Economic Growth in Nigeria. This study employed the ex-post fact research design. Secondary data was obtained from Central Bank of Nigeria Statistical Bulletin between 1991 to 2022. The data obtained were Credit to Private sector, Credit to Public Sector, Total Credit to the Economy, Broad Money Supply and Prime Lending Rate as well as the Real Gross Domestic Product. Series of statistical tests such pre-estimation test (descriptive test, normality test and stationarity test), standard econometric tests (Long-Run and Short-Run regression tests, correlation test as well as granger causality test) and post-estimation tests (such as Multicollinearity test, Serial Correlation LM Test and Heteroskedasticity Test) were performed on the data. The results of the inferential tests were used to validate the formulated hypotheses. Thus, four empirical results emerged; first, it was found-out that Private Sector Credits and Public Sector Credits have positive but insignificant impact on the economic growth. Secondly, there is a strong positive correlation between private and public sector credits and lastly, there is bi-directional causality between bank credits and economic growth. Thus, this study concluded that bank credits have not significant impacted on the Nigerian economic growth. Thus, it recommended among others that the government should minimize its borrowings from banks so as to allow the private individuals with productive objectives access credits. It is also recommended that the monetary authorities should endeavour to increase the credits in the economy, so as to allow improved provision of loanable funds available and accessible to the investing public.
Keywords: Banking Sector, Credit, GDP, Development, Nigeria.